LEXICAL-SEMANTIC PECULIARITIES OF TONGUE TWISTERS - Xamzayev Otakhon Erkinovich, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article analyzes the lexical-semantic features of fast sayings. Fast sayings are an interesting and rich field of folklore. They are phonetically complex and help to improve pronunciation. Puns, alliteration, and assonances are common in rapid utterances. The article analyzes the lexical units of fast sayings and their semantic aspects, and how they are related to the cultural heritage of the people is explained through examples.